Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/dsi.2019.55
|View full text |Cite
|
Sign up to set email alerts
|

Game-Based Learning of Knowledge Reuse in Engineering Education

Abstract: This paper presents an educational game fostering a new experience-based approach to teaching knowledge transfer using a codification strategy alone. The goal is to address and highlight some common issues and challenges that occur during knowledge transfer in product development and that are often difficult for especially students to grasp through exclusively a theoretical teaching approach. The game is introduced to 60 students in the final year of their Master's curriculum. In parallel, the game has been ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For this 21 st -century teaching and learning process, it need to address the outcome-based learning of each learner, and the suggested teaching strategy using educational games. Stenholm et al [8] emphasized that all games design elements that align well with established learning theories, such as social constructivism. Further, they concluded that educational games are used for educational purposes: such games can take a variety of forms from card games to board or digital games.…”
Section: Literature Reviewedmentioning
confidence: 99%
“…For this 21 st -century teaching and learning process, it need to address the outcome-based learning of each learner, and the suggested teaching strategy using educational games. Stenholm et al [8] emphasized that all games design elements that align well with established learning theories, such as social constructivism. Further, they concluded that educational games are used for educational purposes: such games can take a variety of forms from card games to board or digital games.…”
Section: Literature Reviewedmentioning
confidence: 99%